The effectiveness of psychoanalytic psychotherapy in individuals diagnosed with PTSD due to torture and severe human right violations - İlker Özyıldırım; Saliha Baykara; Banu Aslantaş Erteki; Zerrin Oğlagu; Baran Gürsel; Deniz Akyıl; Lale Orhon Baykal; Elif Yıldırım; Bilal Yıldız (Torture)
Abstract